Iqro Method A Quick Way To Learn To Read The Holly Al-Qur’an - Wahyudin*, Yuyu; Syairozi, Ishak; Qutub, Sayid (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
The Iqro method is a phenomenal finding from KH. As'ad Humam on how to read the Qur'an. The Iqro method is highly favored by Muslims as it is proven that millions of copies of Iqro books have been printed,this is because the Iqro method has provided a real solution to overcoming illiterate reading of the Qur'an in an easy, simple, practical way.This is the background for writing this theme in the form of articles.The purpose of this research is for readers to get a correct understanding of the meaning of methods, books and teaching materials. So that Iqro book users know the features and advantages.So that readers know the secret behind Iqro's best-selling book sales.This study uses a qualitative / inductive method approach.Researchers will collect data related to themes in various media: the Internet, journals, books, and other sources in Indonesia from 1990M to January 2023M.The collected data will be reviewed and analyzed. Data related to the title will be used, while data that is not important will be reduced.With qualitative / inductive methods, researcher is sure to arrive at correct and accurate conclusions.